2021
DOI: 10.36076/ppj.2021.24.425
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Systematic Review and Meta-Analysis of 3 Routes of Administration of Epidural Injections in Lumbar Disc Herniation

Abstract: BACKGROUND: The Best Practices in Pain Management from the U.S. Department of Health and Human Services (HHS) describes interventional techniques as part of a continuum. Epidural injections are commonly utilized modalities in managing low back and lower extremity pain. Epidural injections were initially administered in 1901 where the first descriptions of caudal epidural with local anesthetic for low back pain appeared. Since then, multiple developments have occurred. Currently, epidural injections are provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…TESI. Other epidural injection techniques, such as caudal epidural approach [ 45 ] or echography- guided transforaminal approach [ 46 ], might further reduce costs and improve the cost-effectiveness of epidural injections. The latter techniques were not chosen because in The Netherlands there is a strong preference for TESI (usual care within the Pain Department).…”
Section: Discussionmentioning
confidence: 99%
“…TESI. Other epidural injection techniques, such as caudal epidural approach [ 45 ] or echography- guided transforaminal approach [ 46 ], might further reduce costs and improve the cost-effectiveness of epidural injections. The latter techniques were not chosen because in The Netherlands there is a strong preference for TESI (usual care within the Pain Department).…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness studies suggest that patients with acute pain have improved outcomes following epidural (NICE, 2016;updated 2020), with 70%-80% of patients reported to achieve more than 50% improvement in pain and function following injection (Manchikanti et al, 2010). Although the topic remains controversial, Manchikanti et al (2021a) (Bernstein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although the topic remains controversial, Manchikanti et al. (2021a) and Manchikanti et al. (2021b) assert that image‐guided injections of corticosteroids, with or without local anaesthetics, into various locations of the spine provide at least short‐ and intermediate‐term pain relief.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] A large number of meta-analysis and randomized controlled trials showed that acupuncture, massage, traditional Chinese medicine, epidural injections and non steroidal anti-inflammatory drugs have a clear curative effect on LDH, which provides an optional treatment scheme for patients. [9][10][11][12][13] However, a network meta-analysis showed that the effect of oral Chinese medicine is lower than that of acupuncture and massage, but there is insufficient evidence to this conclusion for acute LDH. [14] Recent animal studies have shown that Yaobitong capsule can inhibit the inflammatory response and neuropathy of herniated intervertebral disc.…”
Section: Introductionmentioning
confidence: 99%